The tertiary relicts in woods of the Chechen Republic and Ingushetia - B. A. Hasuyeva; M. A. Astamirova; A. A. Teymurov (Юг России: экология, развитие)
In article data on new sites of tertiary relicts are resulted and the state of their populations is characterised.